Hydro Quest as a Construct 2-based Interactive Multimedia for Statics Fluid Learning - Soraya, Silvi; Kusumah, Fuji Herawati (Jurnal Pendidikan Matematika dan Sains, 2026)
This study aimed to develop Hydro Quest, a Construct 2-based interactive multimedia for static fluid learning, and examine its feasibility, practicality, and potential to support students’ cognitive achievement. Grounded in Multimedia Learning Theory, constructivist learning principles, and gamification concepts, Hydro Quest integrates concept visualization, simulations, electronic worksheets, game-based formative assessment, and immediate feedback within a single learning environment. This Research and Development study employed the DDD-E model (Decide, Design, Develop, and Evaluate). The participants consisted of five expert validators, two physics teachers, 10 students in a small-scale evaluation, and 36 students in a large-scale evaluation. Data were collected through interviews, questionnaires, validation sheets, and cognitive tests. The media achieved Aiken’s V values of 0.86, 0.85, and 0.88 for content, media, and language aspects, respectively. Teacher and student responses ranged from 84.75% to 92.71%, indicating high practicality. Learning outcomes were higher at post-test than at pre-test following the implementation of Hydro Quest, as indicated by a mean n-Gain of 0.67, statistically significant differences as indicated by the Wilcoxon signed-rank test (small-scale: Z = -2.810, p = .005; large-scale: Z = -5.241, p < .001), and large effect sizes (r = 0.889 and 0.874). These findings indicate that Hydro Quest is a feasible and practical learning medium with the potential to support static fluid learning.